ANALISIS TUTURAN KARAKTER TSUNDERE (Pendekatan Pragmatik) - Dewi Saparina Halibanon; Endah Nur Safariyah (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
The title of this study is “Tsundere Character’s utterance analysis: Pragmatic Approach”.The data of this study were dialogic discourse which analyzed using descriptive qualitative methods. The data were collected using observation and writing technique. The data of nonverbal communication documented through photos using a recording technique. The results obtained from this study is the writer in this study focus on 2 points which are verbal utterance and nonverbal behaviour. Firstly, on tsundere verbal utterance studied result as from 19 dialogic discourse almost all of tsundere expression’s characteristic from Togashi theory were found, except for temoii. Secondly, from 5 type illocution by Searle, this research found that tsundere’s speaker use 3 type illocution in utterance, which are asertive, directive, and expressive. Thirdly, to be able convey communication purpose to hearer, tsundere’s speaker use some word that can be used to denial the former statement, such as”~ eba”,”kedo”,”sa”, and “towaie”.From nonverbal behaviour, firstly this study shows that there are 2 response from 3F response by Navarro is found. These response are freeze and flight’s response. Other than that, on every tsundere speaker’s utterance, self calming behaviour, and emphasis were found. Secondly, the last point from nonverbal behaviour is suitability of nonverbal behaviour and verbal utterance. But 19 from 19 discourse, the writer found that tsundere’s speaker tend to utter and act differently and contrary to each other.